2020
DOI: 10.1093/biosci/biaa131
|View full text |Cite
|
Sign up to set email alerts
|

Three Frontiers for the Future of Biodiversity Research Using Citizen Science Data

Abstract: Citizen science is fundamentally shifting the future of biodiversity research. But although citizen science observations are contributing an increasingly large proportion of biodiversity data, they only feature in a relatively small percentage of research papers on biodiversity. We provide our perspective on three frontiers of citizen science research, areas that we feel to date have had minimal scientific exploration but that we believe deserve greater attention as they present substantial opportunities for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(78 citation statements)
references
References 73 publications
0
61
0
2
Order By: Relevance
“…Temporally, many citizen science datasets are biased because participants frequently sample on weekends 14 or disproportionately during specific times of the year such as spring migration for birds 15 , or during specific times of day, such as the morning period when birds are most active. Spatially, there is often a disproportionate number of sightings from areas with large human populations 16 , areas with more accessibility 17 , regions with high biodiversity that attract observers 18 , and regions of the world with higher socioeconomic status 19 . Taxonomic biases also exist as some taxa receive orders of magnitude more citizen science observations than other taxa, evidenced by the fact that birds represent a disproportionate amount of data in the Global Biodiversity Information Facility 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Temporally, many citizen science datasets are biased because participants frequently sample on weekends 14 or disproportionately during specific times of the year such as spring migration for birds 15 , or during specific times of day, such as the morning period when birds are most active. Spatially, there is often a disproportionate number of sightings from areas with large human populations 16 , areas with more accessibility 17 , regions with high biodiversity that attract observers 18 , and regions of the world with higher socioeconomic status 19 . Taxonomic biases also exist as some taxa receive orders of magnitude more citizen science observations than other taxa, evidenced by the fact that birds represent a disproportionate amount of data in the Global Biodiversity Information Facility 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Quantifying biases in citizen science datasets can help (1) researchers using these data to better account for biases when drawing ecological conclusions, (2) the design and implementation of future citizen science projects, and (3) understand what species or regions may need data collection from professional scientists by understanding the ‘limits’ of citizen science projects 19 . Here, we quantify biases in bird observation data from an unstructured, citizen science project—iNaturalist—with that from a semi-structured one—eBird.…”
Section: Introductionmentioning
confidence: 99%
“…For example, genus Anoplodactylus has been confused with Endeis or Achelia, and Nymphon with Phoxichilidium or Pentanymphon (which has five pairs of legs!). Peter et al (2019Peter et al ( , 2021 and Callaghan et al (2020Callaghan et al ( , 2021 highlighted the defects but also the potential of citizen science in biodiversity and environmental research. Moreover, Changeux et al (2020) demonstrated that, with the support of and after validation by professional scientists, data collected by volunteer naturalist scuba divers can be used to outline ecological biodiversity patterns, but with the taxonomical bias already evidenced in the introduction.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, citizen science is included in only a small proportion of academic research publications (Callaghan et al 2021). One of the main barriers for use of citizen science has been the question on data quality.…”
Section: Discussionmentioning
confidence: 99%